Stabilization of Sizing of Waste Paper Containerboard during Storage - Victoria V. Gorazdova; Elena V. Dernova; Dmitriy A. Dulkin (Лесной журнал)
This article is devoted to the study of the mechanism of containerboard sizing. As practice shows, AKD glue (alkyl ketenedimer dispersion) does not fully mature on a paper-making machine and the final sizing in paper and cardboard on the reel is not achieved. The rate of interaction of AKD glue with the hydroxyl groups of cellulose and water is low and, depending on the paper storage temperature, the process can take from several hours to several days. As a rule, after 2 weeks the manufacturer has the final result of sizing in the material, but more often the finished products do not remain in warehouses for a long time, but are sent to the consumer immediately after manufacture. In order to predict the expected level of hydrophobic properties of containerboard after the complete maturation of AKD glue, an express method has been used to determine the absorbency with one-sided wetting according to the Cobb method. This method involves heat treatment at a temperature of 105 ± 2 °C, after which the reaction of the AKD wax with the paper components is completed, and the absorbency of the paper no longer decreases. However, in real conditions of paper and cardboard storage, unfortunately, the results obtained by the express method do not always correspond to the actual absorbency. This is due to the fact that in reality paper and cardboard mature differently than during heat treatment. At the same time, in practice, the following problems with the absorbency are sometimes encountered by the end consumer: under- and over-maturation of AKD glue, as well as reversal of sizing. Therefore, it is important for the manufacturer to evaluate how the maturation of AKD glue occurs and how this process can be optimized and stabilized during storage. The conducted scientific research is aimed at predicting and regulation of the set of considered properties of containerboard and the container itself, which they will achieve after shipment to the consumer due to the long maturation process of the glue used for sizing, depending on the choice of chemical auxiliaries and their dosing options. The possibility of using an express method for determining the surface one-sided absorbency to predict a number of normalized physical and mechanical parameters of future containers is substantiated.